The Board Gender Diversity, Independent Commissioners, Size of Commissioners Board, and Inventory Intensity on Tax Aggressiveness - Novitasari, Desi; Hidayati, Wahyu Nurul (EAJ (Economic and Accounting Journal), 2022)
This study aims to empirically prove the effect of the gender diversity of the board, independent commissioners, size of the board of commissioners, and inventory intensity on tax aggressiveness. The independent variables used in this study are gender diversity of the board, independent commissioners, size of the board of commissioners, and inventory intensity. In contrast, the dependent variable is tax aggressiveness. The population in this study are companies in the property, real estate, and building construction sectors listed on the Indonesia Stock Exchange for 2017-2021. The sample selection method used purposive sampling; based on this method, 31 companies were obtained. The data used in this research is secondary data in the form of annual financial reports. The data analysis method used is descriptive statistics, classical assumption test, and panel data regression test using statistical calculations with the application of Eviews version 10. The study results show that gender diversity on the board does not affect tax aggressiveness. Independent commissioners have a positive effect on tax aggressiveness. The size of the board of commissioners has a positive effect on tax aggressiveness. Inventory intensity has a positive effect on tax aggressiveness. Gender diversity of the board, independent commissioners, size of the board of commissioners, and inventory intensity significantly affect tax aggressiveness.